Performance of Police Members : How The Role of Motivation, Competency and Compensation? - Vita Mayastinasari (Journal of Industrial Engineering & Management Research, 2023)
The purpose of this research is to analyze the relationship between motivation and police performance, competency and police performance, compensation and police performance. This research method is a quantitative survey. Respondents in this study were 310 police officers. Samples were taken based on random sampling technique. Data was obtained by distributing online questionnaires through social media, online questionnaires were designed using a Likert scale of 1 to 7. Data analysis used structural equation modeling ( SEM) with SmartPLS 3.0 software tools. Test research instruments with validity and reliability tests and hypothesis testing. The data analysis technique used in this research is quantitative analysis. In this study the analysis used to determine the effect of work motivation, competence and compensation on the performance of police officers. The results of this study are motivation has a positive and significant effect on police performance, competency has a positive and significant effect on police performance, compensation has a positive and significant effect on police performance.